2000
DOI: 10.1289/ehp.00108641
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Pyrene Exposure of Grass Shrimp, Palaemonetes pugio, Affects Molting and Reproduction of Exposed Males and Offspring of Exposed Females

Abstract: The objective ofthis study was to investigate the impact oflong-term pyrene exposure on molting and reproduction in the model estuarine invertebrate, the grass shrimp (Palaemonetes pugto).Grass shrimp were exosed to measured concentrations of 5.1, 15.0, and 63.4 ppb (pg/L) pyrene for 6 wedss, during which time we determined molting and survivorship. At the end of the exposure, we immediately sacrificed some of the shrimp for biomarker (CYP1A and vitellin) analyses.The remaining shrimp were used to analyze fecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 46 publications
(20 citation statements)
references
References 34 publications
1
19
0
Order By: Relevance
“…The wild shrimp in the current study were collected in August, 4 or 5 months into their reproductive season; thus, the fecundity values do not represent their first brood of the season which may explain why a significant difference in relative fecundity among sites was not observed in East Bay. Furthermore, fecundity may not be the best indicator of exposure to natural or anthropogenic compounds in grass shrimp; females exposed to pyrene (Oberdorster et al 2000), mercury and PCBs (Wall et al 2001), the insecticide endosulfan (Wirth et al 2002) and the pesticides chloropyrifos and fipronil (Volz et al 2003) in the laboratory did not show a reduction in fecundity compared to controls.…”
Section: Morphometric and Reproductive Parameters Of Wild-caught Shrimpmentioning
confidence: 99%
“…The wild shrimp in the current study were collected in August, 4 or 5 months into their reproductive season; thus, the fecundity values do not represent their first brood of the season which may explain why a significant difference in relative fecundity among sites was not observed in East Bay. Furthermore, fecundity may not be the best indicator of exposure to natural or anthropogenic compounds in grass shrimp; females exposed to pyrene (Oberdorster et al 2000), mercury and PCBs (Wall et al 2001), the insecticide endosulfan (Wirth et al 2002) and the pesticides chloropyrifos and fipronil (Volz et al 2003) in the laboratory did not show a reduction in fecundity compared to controls.…”
Section: Morphometric and Reproductive Parameters Of Wild-caught Shrimpmentioning
confidence: 99%
“…Gender-specific induction of ECOD was detected by Oberdorster et al (2000a) in P. pugio when exposed to pyrene at 63 ppb. In that study, pyrene induced ECOD activity in males only.…”
Section: Discussionmentioning
confidence: 93%
“…Although the life cycle of P. australis has been poorly studied in estuaries of southwest Western Australia, this study found it to be easily maintained in the laboratory, making it an ideal candidate for the study of the impact of contaminant exposure on the health of this estuarine decapod species. PAHs have been shown to significantly induce CYP1A-like protein (P450) activity in grass shrimp (P. pugio) as measured by ECOD in hepatopancreatic extracts (Oberdorster et al 2000a). Investigations elsewhere have indicated that blue crabs (Callinectes sapidus) were unable to metabolize and eliminate PAHs the closer they were to molting, resulting in a higher body burden (Mothershead and Hale 1992).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations